The Development of Practice Packages on Chinese Pronunciation Skills through Seesaw Online Classroom for Students Majoring in Chinese Language Teaching - Chanpeng , Pantipa (Asian Journal of Education and Training, 2022)
This research aimed to 1) develop and measure the efficiency of a set of reading and pronunciation skills in Chinese phonetics via Seesaw online classroom; 2) examine the effectiveness of the set; and 3) evaluate students’ satisfaction with practice packages on Chinese pronunciation via Seesaw online classroom. Thirty-six undergraduate students majoring in Chinese language teaching at a university in Thailand were the participants of this study. This study used descriptive statistics (mean and S.D.) and dependent samples t-test. The results of this research indicated a substantial increase in students’ learning achievement due to the Seesaw online classroom. Additionally, the Development of Practice Packages for Chinese Pronunciation Skill Acquisition via Seesaw Online Classroom was greater (x̄=4.84, S.D.=0.37) than the researcher’s standard of 3.50, and achieved the efficiency standard criteria of 82.50/84.97, which was greater than the 80/80 efficiency standard criterion chosen. Students’ satisfaction with learning was high when they utilized Seesaw’s Chinese pronunciation practice packages (x̄= 4.50, S.D.= 0.54).